2015
DOI: 10.3892/or.2015.4187
|View full text |Cite
|
Sign up to set email alerts
|

Never in mitosis gene A-related kinase 6 and aurora kinase A: New gene biomarkers in the conversion from ulcerative colitis to colorectal cancer

Abstract: Ulcerative colitis (UC) is an important risk factor for colorectal cancer (CRC). Histone modifications are one of the epigenetic mechanisms that may have key roles in the carcinogenesis of CRC. At present, there are no studies comparing histone modification patterns of UC and CRC in the literature. Therefore the aim of the present study was to investigate whether genes, particularly those involved in histone modification, have value in patient monitoring with regards to CRC development in UC. Key gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…In recent years, altered expression and activity of NEK6 were associated with several types of cancer, such as liver [139], prostate [140], gastric [141][142][143], colorectal [144,145], breast [146], serous epithelial ovarian [147], thyroid [148], and retinoblastoma cancers [149]. In addition, inflammation-based diseases, such as ulcerative colitis, have also been linked to NEK6 [28].…”
Section: Nek6mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, altered expression and activity of NEK6 were associated with several types of cancer, such as liver [139], prostate [140], gastric [141][142][143], colorectal [144,145], breast [146], serous epithelial ovarian [147], thyroid [148], and retinoblastoma cancers [149]. In addition, inflammation-based diseases, such as ulcerative colitis, have also been linked to NEK6 [28].…”
Section: Nek6mentioning
confidence: 99%
“…NEK6 was found to be overexpressed in patients with more extensive colon involvement and long-term ulcerative colitis. It was suggested that NEK6 is involved in the early stages of inflammation associated with CRC development in UC patients [28]. Thus, NEK6 could be an early marker of CRC in patients with ulcerative colitis.…”
Section: Nek6mentioning
confidence: 99%
“…16,17 AURKB, a member of the aurora kinase family, is an important diagnostic and prognostic marker involved in the carcinogenesis of colorectal cancers. 18 FOXQ1 is frequently upregulated in colorectal cancers, and FOXQ1 knockdown suppressed cell proliferation and the migration and invasion of colorectal cancers. 19 TOP2A is a potential predictive biomarker for anthracycline and irinotecan treatment in colorectal cancer, and high frequency of gene gains for the TOP1 and TOP2A genes were reported in colorectal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CDK1 is overexpressed in human colorectal cancers and relevant to the clinical behavior of human colorectal cancers, which was shown by the association between a high ratio of CDK1 nuclear to cytoplasmic expression and poor overall survival and that CDK1 was an independent risk factor for outcome . AURKB, a member of the aurora kinase family, is an important diagnostic and prognostic marker involved in the carcinogenesis of colorectal cancers . FOXQ1 is frequently upregulated in colorectal cancers, and FOXQ1 knockdown suppressed cell proliferation and the migration and invasion of colorectal cancers .…”
Section: Discussionmentioning
confidence: 99%
“…Drinking and smoking are also risk factors. Except the environmental factors, patients with familial adenomatous polyposis or ulcerative colitis often progress to colon carcinoma. Furthermore, a hereditary predisposition has also been reported .…”
mentioning
confidence: 99%